Boost your brain: a simple 100% normobaric oxygen treatment improves human motor learning processes - Zheng Wang; Guillaume Spielmann; Guillaume Spielmann; Neil Johannsen; Neil Johannsen; Frank Greenway; Brian A. Irving; Brian A. Irving; Marc Dalecki (Frontiers in Neuroscience, 2023)
IntroductionHuman motor learning processes are a fundamental part of our daily lives and can be adversely affected by neurologic conditions. Motor learning largely depends on successfully integrating cognitive and motor-related sensory information, and a simple, easily accessible treatment that could enhance such processes would be exciting and clinically impactful. Normobaric 100% oxygen treatment (NbOxTr) is often used as a first-line intervention to improve survival rates of brain cells in neurological trauma, and recent work indicates that improvements in elements crucial for cognitive-motor-related functions can occur during NbOxTr. However, whether NbOxTr can enhance the motor learning processes of healthy human brains is unknown. Here, we investigated whether a brief NbOxTr administered via nasal cannula improves motor learning processes during a visuomotor adaptation task where participants adapt to a visual distortion between visual feedback and hand movements.Methods40 healthy young adults (M = 21 years) were randomly assigned to a NbOxTr (N = 20; 100% oxygen) or air (N = 20; regular air) group and went through four typical visuomotor adaptation phases (Baseline, Adaptation, After-Effect, Refresher). Gas treatment (flow rate 5 L/min) was only administered during the Adaptation phase of the visuomotor experiment, in both groups.ResultsThe NbOxTr provided during the Adaptation phase led to significantly faster and about 30% improved learning (p < 0.05). Notably, these motor learning improvements consolidated into the subsequent experiment phases, i.e., after the gas treatment was terminated (p < 0.05).DiscussionWe conclude that this simple and brief NbOxTr dramatically improved fundamental human motor learning processes and may provide promising potential for neurorehabilitation and skill-learning approaches. Further studies should investigate whether similar improvements exist in elderly and neurologically impaired individuals, other motor learning tasks, and also long-lasting effects.